Can household clean energy transition reduce medical expenditures? Evidence from China - Tao Li; Dan Xiao Yang (Frontiers in Public Health)
Indoor air pollution is a significant issue in developing nations, posing serious health risks and contributing to various diseases. Despite its importance, the relationship between household clean energy transition and its effects on health outcomes and medical expenses has received limited scholarly attention. This study addresses this gap by utilizing the Air Pollution Prevention and Control Action Plan (APCP), implemented by the State Council of China in 2013, as a policy intervention. Using data from the China Family Panel Studies (CFPS) spanning from 2014 to 2020, a staggered Difference-in-Differences (DID) model was developed to assess the impact of the transition to clean energy on medical expenses. The findings indicate that household clean energy transition can significantly reduce residents’ medical expenditures. Heterogeneity analyses indicate that rural populations, individuals with lower educational attainment, homeowners, and families consisting of three to five members experience a more significant reduction in medical costs associated with household clean energy transition. Mechanism analysis reveals that the reduction in medical costs is attributable to the improvements in health outcomes and increases in income resulting from the clean energy transition. This study offers a significant academic foundation and support for developing countries in formulating clean energy and health policies.